Different Fast-Gate Regulation by External Cl(−) and H(+) of the Muscle-Type Clc Chloride Channels - Chen, Mei-Fang (The Rockefeller University Press, 2001)
The fast gate of the muscle-type ClC channels (ClC-0 and ClC-1) opens in response to the change of membrane potential (V). This gating process is intimately associated with the binding of external Cl(−) to the channel pore in a way that the occupancy of Cl(−) on the binding site increases the channel's open probability (P (o)). External H(+) also enhances the fast-gate opening in these channels, prompting a hypothesis that protonation of the binding site may increase the Cl(−) binding affinity, and this is possibly the underlying mechanism for the H(+) modulation. However, Cl(−) and H(+), modulate the fast-gate P (o)-V curve in different ways. Varying the external Cl(−) concentrations ([Cl(−)](o)) shifts the P (o)-V curve in parallel along the voltage axis, whereas reducing external pH mainly increases the minimal P (o) of the curve. Furthermore, H(+) modulations at saturating and nonsaturating [Cl(−)](o) are similar. Thus, the H(+) effect on the fast gating appears not to be a consequence of an increase in the Cl(−) binding affinity. We previously found that a hyperpolarization-favored opening process is important to determine the fast-gate P (o) of ClC-0 at very negative voltages. This [Cl(−)](o)-independent mechanism attracted little attention, but it appears to be the opening process that is modulated by external H(+).